Hack proofing your identity in the information age protect your family on the internet! - Bidwell, Teri.; Cross, Michael, 1965-; Russell, Ryan, 1969- (Rockland, MA : Syngress, 2002)
Identity-theft is the fastest growing crime in America, affecting approximately 900,000 new victims each year. Protect your assets and personal information online with this comprehensive guide. Hack Proofing Your Identity will provide readers with hands-on instruction for how to secure their personal information on multiple devices. It will include simple measures as well as advanced techniques gleaned from experts in the field who have years of experience with identity theft and fraud. This book will also provide readers with instruction for identifying cyber-crime and the different ways they can report it if it occurs. Hot Topic. Hack Proofing Your Identity will provide readers with both simple and advanced steps they can take to protect themselves from cyber-crime. Expert Advice. This book will present security measures gathered from experts in both the federal government and the private sector to help secure your personal information and assets online. Unique Coverage. Hack Proofing Your Identity will be the only book to include security measure for multiple devices like laptops, PDAs and mobile phones to allow users to protect themselves while taking advantage of the newest ways to access the Internet.
Identity theft : are you at risk? -- Protecting your hard drive -- Keeping your e-mail private -- Self defense on the web -- Connecting to the Internet safely -- Are your kids putting you at risk? -- If you become a victim -- Configuring your browser and firewall.
Includes index.
Keywords: Computer security; Identification cards -- Forgeries; Internet fraud; Computer crimes; Impostors and imposture; Electronic books